Maxim of Politeness in â€œSpies In Disguiseâ€ Movie - Sakti, Anak Agung Bagus Wahana; Aryani, I Gusti Agung Istri; Putra, I Komang Sumaryana (LPPM Universitas Dhyana Pura, 2023)
This study entitled Maxim of Politeness in â€œSpies In Disguiseâ€ Movie. This study focusses on the find out the types of politeness maxim applied by the characterâ€™s conversation in the â€œSpies In Disguiseâ€ movie. The aim is to identify the type of maxim used in the conversation that occurs with the characters in the movie